Effect of Sub-maximal Exercise Stress on Cold Pressor Pain: A Gender Based Study - Pokhrel, BR; Malik, SL; Ansari, AH; Paudel, BJ; Sinha, R; Sinha, M (Kathmandu University Medical Journal, 2014)
Background Analgesic effect of exercise is a well established fact; however available reports are contradictory on gender differences in pain perception following exercise stress test. Objective The current study is prospectively designed to evaluate and compare the effect of acute bout of sub-maximal exercise stress on cold pressor pain in normal adult males and females. Method The experimental study design involved healthy adults (n= 41); females (n = 18) and males (n=23) aged between 18 to 25 years and included them into four sets of experiments: SET I (Control), “resting blood pressure, radial pulse and respiratory rate were recorded after 15 minutes of complete supine relaxation. SET II (Cold Pressor Pain Test): Pain Threshold, Pain Tolerance, and Pain Duration in seconds were taken. SET III (Exercise Stress Test): Sub-maximal exercise of 70 to 75% of maximum predicted heart rate was given for 6 minutes. SET IV (Cold Pressor Pain Test immediately after Exercise Stress Test): At 0 minute of recovery again the pain parameters; Pain Threshold, Pain Tolerance, and Pain Duration in seconds were taken. SET I, SET II were performed in order on the first day and SET III and SET IV on the second day to ensure only a single Cold Pressor Pain Test is performed in each day. Result The data (Mean ±SD) analysis showed significant increased in pain threshold (males: 14.36±10.6 Vs 21.47±13seconds, p<0.001, females: 14.1±11.5 Vs 23.81± 20.22 seconds, p<0.001) and pain tolerance time (males: 41.3±19.31Vs 54.1±21.7 seconds, p<0.001) in both sexes after 6 min of acute bout of sub-maximal exercise stress test with comparable age, BMI and baseline resting values of pain parameters and pulse rate and blood pressure. The percentage increment pain tolerance time following the exercise stress in female is higher than male (78.6 Vs 68.9%). Conclusion The result suggests that pain sensation decreases immediately after a brief period of exercise challenge irrespective of gender, and the analgesic effect of the acute bout of exercise in terms of pain tolerant time is more enhanced in females than males. DOI: http://dx.doi.org/10.3126/kumj.v11i1.11028 Kathmandu University Medical Journal Vol.11(1) 2013: 54-59